Targeting GPCRs Against Cardiotoxicity Induced by Anticancer Treatments - Audebrand, Anais; Désaubry, Laurent; Nebigil, Canan G. (Frontiers in Cardiovascular Medicine, 2020)
Novel anticancer medicines, including targeted therapies and immune checkpoint inhibitors, have greatly improved the management of cancers. However, both conventional and new anticancer treatments induce cardiac adverse effects, which remain a critical issue in clinic. Cardiotoxicity induced by anti-cancer treatments compromise vasospastic and thromboembolic ischemia, dysrhythmia, hypertension, myocarditis, and cardiac dysfunction that can result in heart failure. Importantly, none of the strategies to prevent cardiotoxicity from anticancer therapies is completely safe and satisfactory. Certain clinically used cardioprotective drugs can even contribute to cancer induction. Since G protein coupled receptors (GPCRs) are target of forty percent of clinically used drugs, here we discuss the newly identified cardioprotective agents that bind GPCRs of adrenalin, adenosine, melatonin, ghrelin, galanin, apelin, prokineticin and cannabidiol. We hope to provoke further drug development studies considering these GPCRs as potential targets to be translated to treatment of human heart failure induced by anticancer drugs.